Comparative Evaluation Of Physico-Morphological Attributes Of Semen Of Jafarabadi, Mehsana (Bubalus Bubalis) And Crossbred (Hf X Kankrej) (Bos Indicus) Bulls - Patel, J. B.; Dhami, A. J.; Patel , P. A. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
Semen ejaculates (90) of 15 mature bulls, 5 each of Jafarabadi, Mehsana and Crossbred (HF x Kankrej, F1) breeds collected at weekly interval during autumn season were studied for HOS test and physico-morphological attributes of spermatozoa and their interrelationships. The mean ejaculate volume (ml), mass activity (score 0-5), individual sperm motility (%), sperm concentration (million/ml), live sperm (%), abnormal sperm (%) and HOS reactive sperm (%) in Jafarabadi buffalo bulls semen were 4.81 ± 0.21, 3.30 ± 0.08, 74.33 ± 0.75, 1466.80 ± 72.43, 84.93 ± 0.59, 10.67 ± 0.43 and 70.47 ± 0.54, respectively. The corresponding values for Mehsana buffalo bulls semen were 5.01 ± 0.23, 3.23 ± 0.12, 73.83 ± 0.67, 1307.43 ± 94.27, 82.47 ± 0.67, 10.83 ± 0.38 and 71.53 ± 0.89; and in HF x K Crossbred bulls semen 6.68 ± 0.31, 2.83 ± 0.09, 72.00 ± 0.51, 1094.80 ± 78.85, 79.60 ± 0.65, 12.87 ± 0.45 and 61.37 ± 0.69, respectively. The three breeds varied significantly (P < 0.01) in their seminal attributes. The ejaculate volume and abnormal sperm per cent were significantly (P<0.05) higher in crossbreds as compared to buffalo bulls, whereas the values of all other traits were significantly (P<0.01) higher in buffalo bulls, particularly in Jafarabadi breed, as compared to crossbreds. The ejaculate volume had significant negative correlations (P < 0.05) with most traits in all the three breeds; while mass activity showed significant positive correlations with initial motility, sperm concentration and live sperm percentage. The motility and sperm concentration were positively (P<0.01) associated, while live sperm and abnormal sperm were negatively (P<0.05) correlated in all three breeds. HOS reactive sperms, however, did not reveal high significant correlations with other traits in any of the breeds studied. Semen quality of Jafarabadi bulls was optimum, followed by Mehsana buffalo and that of crossbred bulls was relatively inferior.